2018
DOI: 10.1128/jvi.00681-18
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Variation at VP1-145 of Enterovirus 71 Determines Attachment Receptor Usage and Neurovirulence in Human Scavenger Receptor B2 Transgenic Mice

Abstract: Infection of enterovirus 71 (EV71) is affected by cell surface receptors, including the scavenger receptor B2, which are required for viral uncoating, and attachment receptors, such are heparan sulfate (HS), which bind virus, but do not support uncoating. Amino acid residue 145 of the capsid protein VP1 affects viral binding to HS, and virulence in mice. However, the contribution of this amino acid to pathogenicity in humans is not known. We produced EV71 having glycine (VP1-145G) or glutamic acid (VP1-145E) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 49 publications
2
84
1
Order By: Relevance
“…Therefore, HS is not expressed at high levels in SCARB2-positive neuronal cells. The distributions of HS and SCARB2 in monkeys are similar to those in hSCARB2 tg mice (28), suggesting that the HS attachment receptor does not contribute to productive infection mediated by SCARB2 in neuronal cells in vivo. Production of neutralizing antibody against EV71.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Therefore, HS is not expressed at high levels in SCARB2-positive neuronal cells. The distributions of HS and SCARB2 in monkeys are similar to those in hSCARB2 tg mice (28), suggesting that the HS attachment receptor does not contribute to productive infection mediated by SCARB2 in neuronal cells in vivo. Production of neutralizing antibody against EV71.…”
mentioning
confidence: 78%
“…Using an hSCARB2 tg mouse model, Kobayashi et al (28) found that VP1-145G viruses bind to HS and that HS is expressed highly in cells that do not express SCARB2. HSs act as decoys that trap the VP1-145G viruses and prevent their spread in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This gives rise to a low viremia level with a substantial reduction of virulence in mice. Kobayashi and colleagues reported that EGK virus is less virulent compared to EEK due to the former harbouring the VP1-G145 residue, enabling the virus to adsorb more strongly to HS, resulting in attenuated virulence in SCARB2-expressing transgenic mice [56]. Our findings that a strong heparin-binding phenotype attenuates virulence is also observed in other viruses, including Sindbis virus [33], Venezuelan equine encephalitis virus [55], West Nile virus [30], yellow fever virus [31] and Japanese encephalitis virus [57].…”
Section: Discussionmentioning
confidence: 99%